(633) Competitive Industry صناعة تنافسية - W. Stonier, Alfred; C. Hague, Douglas (INP, 2024)
This study discusses the definition of pure and perfect competition, starting with an exploration of the meaning and structure of various curves necessary for understanding equilibrium conditions in firms and industries. It focuses on analyzing how firms reach equilibrium under keen competition. The text highlights that competitive conditions reveal the fundamental features of firm equilibrium, regardless of whether the conditions are competitive or monopolistic. Competitive conditions are defined more precisely, noting that demand for individual firms' products is infinitely elastic, allowing them to sell as much as they wish at the existing market price without altering it. Three fundamental prerequisites for the existence of pure competition among producers are outlined, contributing to a better understanding of how competitive markets function.